Socioeconomic status, race and COPD health outcomes. Issue 1 (23rd October 2009) - Eisner, M D; Blanc, P D; Omachi, T A; Yelin, E H; Sidney, S; Katz, P P; Ackerson, L M; Sanchez, G; Tolstykh, Irina; Iribarren, C
Abstract : Background: Although chronic obstructive pulmonary disease (COPD) is a common cause of death and disability, little is known about the effects of socioeconomic status (SES) and race–ethnicity on health outcomes. Methods: The aim of this study is to determine the independent impacts of SES and race–ethnicity on COPD severity status, functional limitations and acute exacerbations of COPD among patients with access to healthcare. Data were used from the Function, Living, Outcomes and Work cohort study of 1202 Kaiser Permanente Northern California Medical Care Plan members with COPD. Results: Lower educational attainment and household income were consistently related to greater disease severity, poorer lung function and greater physical functional limitations in cross-sectional analysis. Black race was associated with greater COPD severity, but these differences were no longer apparent after controlling for SES variables and other covariates (comorbidities, smoking, body mass index and occupational exposures). Lower education and lower income were independently related to a greater prospective risk of acute COPD exacerbation (HR 1.5; 95% CI 1.01 to 2.1; and HR 2.1; 95% CI 1.4 to 3.4, respectively). Conclusion: Low SES is a risk factor for a broad array of adverse COPD health outcomes. Clinicians and disease management programs should consider SES as a key patient-level marker of risk for poor outcomes.